Formation of electron beam fields with 3D printed filters - Miloichikova I. A. Irina Alekseevna; Krasnykh A. A. Angelina Aleksandrovna; Danilova I. Irina; Stuchebrov S. G. Sergey Gennadevich; Kudrina V. Veronika (Simulation and modeling in materials engineering, 2016)
Title screen